2022
DOI: 10.1002/jcsm.13067
|View full text |Cite
|
Sign up to set email alerts
|

The time course of disuse muscle atrophy of the lower limb in health and disease

Abstract: Short, intermittent episodes of disuse muscle atrophy (DMA) may have negative impact on age related muscle loss. There is evidence of variability in rate of DMA between muscles and over the duration of immobilization. As yet, this is poorly characterized. This review aims to establish and compare the time‐course of DMA in immobilized human lower limb muscles in both healthy and critically ill individuals, exploring evidence for an acute phase of DMA and differential rates of atrophy between and muscle groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Future meta‐analyses could complement our findings by incorporating single‐leg disuse models involving injured participants to ascertain whether similar declines in muscle strength and size occur between injury and non‐injury scenarios of single‐leg muscle disuse. For example, a recent report demonstrated that the critically ill experienced significantly greater rates of lower limb skeletal muscle loss compared with healthy individuals undergoing muscle disuse 16 . This result highlights how our findings in uninjured adults may not necessarily recapitulate clinical scenarios of disuse.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Future meta‐analyses could complement our findings by incorporating single‐leg disuse models involving injured participants to ascertain whether similar declines in muscle strength and size occur between injury and non‐injury scenarios of single‐leg muscle disuse. For example, a recent report demonstrated that the critically ill experienced significantly greater rates of lower limb skeletal muscle loss compared with healthy individuals undergoing muscle disuse 16 . This result highlights how our findings in uninjured adults may not necessarily recapitulate clinical scenarios of disuse.…”
Section: Discussionmentioning
confidence: 67%
“…For example, a recent report demonstrated that the critically ill experienced significantly greater rates of lower limb skeletal muscle loss compared with healthy individuals undergoing muscle disuse. 16 This result highlights how our findings in uninjured adults may not necessarily recapitulate clinical scenarios of disuse.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Twenty-three healthy males (age: 22 ± 1 year; height: 179.4 ± 1.3 cm; body mass: 73.4 ± 1.5 kg; body mass index 22.8 ± 0.5 kg•m À2 ) volunteered to take part in this study. Prior to inclusion, participants attended the Nutritional Physiology Research Unit at the University of Exeter for routine medical screening to ensure they did not contravene the following exclusion criteria: diagnosed metabolic impairment (e.g., type 1 or type 2 diabetes); cardiovascular disease; hypertensive (≥140/90 mmHg); chronic use of prescribed or over-the-counter pharmaceuticals; personal or family history of epilepsy, schizophrenia, or seizures; presence of an ulcer in the stomach or gut; pre-existing liver or kidney condition; musculoskeletal injury within 6 months prior to enrolment; having previously received a stable isotope tracer containing 15 N; regular use of nutritional supplements; and/or an allergy or intolerance to lidocaine or amino acids. Written consent was obtained from all participants following full explanation of the experimental procedures, which were approved by the University of Exeter's Sport and Health Sciences Ethics Committee (180509/B/01).…”
Section: Participantsmentioning
confidence: 99%
“…5,10,12 In support, our recent work demonstrated that the decrease in daily MPS rates, which capture multiple postabsorptive and postprandial periods, positively correlate with reductions in muscle volume after 7 days of unilateral leg immobilization (r 2 = 0.417, P < 0.05). 13 It is therefore suggested that this decline in MPS quantitatively accounts for only ~25-50% of the measured muscle loss with short-term (<14 days) disuse 13,14 when the rate of atrophy is greatest, 15,16 although some work has argued MPS can potentially explain an even greater proportion. 12,17 Moreover, marked reductions in muscle volume are evident after only 2 days of immobilization (i.e., ~0.85% per day 18 ) despite less a pronounced decline in daily MPS 13 and can occur in the absence of any changes in MPS if high-volume and high-intensity eccentric contractions are performed before immobilization.…”
Section: Introductionmentioning
confidence: 99%